Determinants of non-performing loans: an empirical study of commercial banks in Malaysia - Ng, Foong Khen (2018)
The financial crises that Malaysia had experienced highlighted the importance of a healthy and resilient banking system, the impact of non-performing loans (NPL) of banks and its link to banking crises. Although NPL is a key financial indicator extensively studied in various countries, studies on NPL of banks in Malaysia are indeed limited. This study aimed to add to the very few studies done and perhaps the first, to examine the determinants of NPL of all the commercial banks in the Malaysian banking system, comparing the differences of determinants between local and foreign-owned commercial banks.